2019
DOI: 10.3390/ijms20133228
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and Cardiovascular Risk. From Pathophysiology to Clinic: Focus on Children and Adolescents

Abstract: Adiponectin (Ad) is a cytokine produced by adipocytes that acts on specific receptors of several tissues through autocrine, paracrine, and endocrine signaling mechanisms. Ad is involved in the regulation of cell survival, cell growth, and apoptosis. Furthermore, Ad plays an important pathophysiological role in metabolic activities by acting on peripheral tissues involved in glucose and lipid metabolism such as skeletal muscle, and the liver. Adiponectin has anti-inflammatory, anti-atherogenic, and insulin-sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 104 publications
2
35
0
Order By: Relevance
“…The HMW adiponectin levels trended higher in females when compared to male participants. Our results are consistent with current data in the general pediatric population 26 , 46 , 52 55 , with obese boys having the lowest levels when compared to girls and lean children, as the androgen rise with puberty in boys is associated with reduced adiponectin level 55 , 56 . In our cohort, the majority of participants were pubertal, and the number of prepubertal subjects was quite small and we could not verify the impact of puberty on adiponectin levels in survivors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The HMW adiponectin levels trended higher in females when compared to male participants. Our results are consistent with current data in the general pediatric population 26 , 46 , 52 55 , with obese boys having the lowest levels when compared to girls and lean children, as the androgen rise with puberty in boys is associated with reduced adiponectin level 55 , 56 . In our cohort, the majority of participants were pubertal, and the number of prepubertal subjects was quite small and we could not verify the impact of puberty on adiponectin levels in survivors.…”
Section: Discussionsupporting
confidence: 92%
“…The Endoplasmic Reticulum Oxidoreductase 1 alpha (Ero1-La) releases the ERp44-bound oligomers 45 . Adiponectin has significant Immunometabolic effects, including actions in insulin sensitivity and inflammation 19 , 46 . The mechanisms of adiponectin downregulation in obesity are not fully understood, but it may be related to adipose tissue macrophage secretion of Tumor Necrosis Factor Alpha (TNFα) and oxidative stress suppressing adiponectin gene expression 47 51 .…”
Section: Discussionmentioning
confidence: 99%
“…This is the first clinical study that has demonstrated the effect of correction of acute hyperglycemia on adiponectin levels. Adiponectin is known to inversely correlate with body weight and abdominal obesity [18]. The decreases in adiponectin levels were independent of BMI in our study.…”
Section: Discussionsupporting
confidence: 68%
“…Adiponectin is the most abundant adipokine produced and secreted by adipocytes. Through binding with its specific receptors adiponectin receptor 1 (AdipoR1) and AdipoR2, adiponectin initiates intracellular signaling pathways and exerts promising effects in the prevention or treatment of diabetes and metabolic syndrome, cardiovascular diseases, cancers, central nervous system disorders and so on [1][2][3][4]. Previous researches have confirmed that adiponectin signaling could be mediated by adaptor protein APPLs (adaptor protein, phosphotyrosine interacting with PH domain and leucine zipper) including APPL1 and APPL2 [5,6].…”
Section: Introductionmentioning
confidence: 99%